2014
DOI: 10.1111/tmi.12377
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patterns of multimorbidity among the elderly in Burkina Faso: cross‐sectional study

Abstract: Abstractobjectives To assess the prevalence and distribution patterns of multimorbidity among urban older adults in Burkina Faso.methods Cross-sectional study among community-dwelling elderly people aged ≥60 in BoboDioulasso. We performed interviews, clinical examination and medical record review. Multimorbidity was defined as co-occurrence of at least two chronic diseases in one person whether as a coincidence or not.results The overall prevalence of multimorbidity among older adults was 65%. Age ≥70 was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 24 publications
4
45
1
2
Order By: Relevance
“…Multimorbidity is a little-explored topic in low-resource settings18 and this is one of the first papers reporting the prevalence of multimorbidity such settings. There has been one previous study from Burkina Faso, conducted in a major city in 2010, which found an even higher prevalence of multimorbidity (65%) than in this study 32. However, the earlier study population was older (>60 years of age) and data were collected on a wider range of conditions, many of which were highly prevalent (eg, osteoarthritis), and which encompassed a range of health states somewhat broader than our definition of a disease (eg, visual impairment, malnutrition).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Multimorbidity is a little-explored topic in low-resource settings18 and this is one of the first papers reporting the prevalence of multimorbidity such settings. There has been one previous study from Burkina Faso, conducted in a major city in 2010, which found an even higher prevalence of multimorbidity (65%) than in this study 32. However, the earlier study population was older (>60 years of age) and data were collected on a wider range of conditions, many of which were highly prevalent (eg, osteoarthritis), and which encompassed a range of health states somewhat broader than our definition of a disease (eg, visual impairment, malnutrition).…”
Section: Discussioncontrasting
confidence: 63%
“…It has a population of about 19 million people which is growing rapidly 30 31. There are few data on the epidemiology of multimorbidity in Burkina Faso, although one study suggested a high prevalence of multimorbidity in an urban setting 32. This study aims to investigate the prevalence and associations (including important downstream consequences of multimorbidity including frailty, disability, quality of life and other measures of physical performance) among middle-aged and older individuals in a rural, very low income setting in Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%
“…6 and West Africa. 24 which observed multimorbidity as 57%, 58% and 65% in the study population respectively. While another study in China by wang et al 25 in 2011 observed a much higher percentage i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Definitional problems aside, conceptualization of multimorbidity began with simple counting of co‐occurring diseases, followed by identifying associations between co‐occurring diseases and identifying causal relations . This approach could be characterized as a unilevel approach to multimorbidity.…”
Section: Conceptualizations Of Multimorbiditymentioning
confidence: 99%
“…Most research has focused at the gene level, identifying clusters of diseases that co‐occur more frequently than by chance alone . A variety of interact‐omics such as genomics, proteomics and metabolomics have served as research targets . In addition, these network structures exist at multiple levels from cellular to societal.…”
Section: Importance Of Network To Underlying Human Health and Diseasementioning
confidence: 99%